Ponderal Effect due to Alkyl Substitution on Physical Constants of Alcohols-A Quantitative Correlation - Jessy, J.M. (Asian Journal of Chemistry, 2010)
The parameter of ponderal substituent effect, log (1/μ), has been shown to give good linear correlations with functions of various physical constants for alcohols of normal series. The functions, in all cases, apparently represent hydrogen-bond strength under the different circumstances of different physical processes. The correlation is therefore suggested to be of ponderal effect on H-bonding.